Management of obstetric nurses in good practices in childbirth and birth (Research, Society and Development, 2020)
The Humanization of childbirth aims to provide comprehensive care, with respect to the parturient and the physiology of the body and the reduction of unnecessary interventions. The aim of this study was to know the scientific production on the management of obstetric nurses in the use of good practices in childbirth and birth. This is a qualitative research, in the form of a review of narrative literature. The initial search consisted of 41 productions in the Lilacs database, 26 productions in the Scielo database and 136 productions in the VHL, with timeframe from 2015. From the establishment of the inclusion and exclusion criteria, the corpus This review comprised a total of 19 articles. The results of the articles were divided into three categories: Performance of obstetric nurses, good practices before and after delivery and obstetric violence. That the insertion of obstetric nurses has marked the predominance of humanized care in delivery and birth care with the use of good practices, respecting the autonomy of the parturient and providing the best possible comfort, and this specialty of obstetric nursing is in a process. transforming his practice towards breaking with the medicalized model.